Menakar Ulang Ekonomi Kerakyatan di Pulau Padang, Riau - Masdar Farid (Brawijaya Journal of Social Science, 2019)
This is related to the existence of financial inclusion from the government which leads to economic improvement for small entrepreneurs in the region. However, the people's economy cannot be absorbed by all groups. In the people of Padang Island, Riau, peopleâ€™s economic policies only apply to minority groups. The group is ethnic Malays and Javanese. While minority groups such as the Akit people (native) group did not get this right. This is because this system is biased towards ethnic problems. Akit people as descendants of Orang Suku Laut (OSL) are considered to have no ability in financial management and business plan. Thus, the cooperative economic system in the village only benefits the majority. The failure of the populist economic system in certain ethnic groups is an important note for the government to overcome ethnic and racial boundaries in carrying out an economy that is friendly to the small people.Keynote: populist economy, Padang Island, Akit people, minority, democracy economy. Â Â